Vortioxetine alleviates motor, cognitive and emotional disorders in post-stroke rats by regulating the TLR-2/NF-κB pathway - Dong, Ziqiang; Dong, Zhihui; Xu, Lili; Zhang, Jinfeng; Li, Lin; Wang, Rongjuan; Huang, Xiaoyan; Zou, Zhengqiang (Frontiers in Pharmacology, 2025)
Cognitive impairments following post-stroke significantly hinder neurological recovery and exacerbate patient morbidity, underscoring urgent need for effective therapeutic strategies. Vortioxetine (VTX), a prominent Selective Serotonin Reuptake Inhibitor (SSRI), boasts notable antidepressant, cognition-enhancing, and anti-inflammatory properties. This investigation delves into VTX’s influence on motor skills, spatial learning-memory capabilities, and depressive behaviors in Middle Cerebral Artery Occlusion (MCAO) rats, alongside its underlying mechanisms. Our findings reveal that while VTX fails to entirely reverse ischemic-reperfusion damage, it substantially ameliorates spontaneous locomotor functions, augments post-stroke learning-memory capacities, and exhibits potent antidepressant and anxiety-like efficacy. Preliminary data propose that these beneficial effects may stem from inflammation modulation via the Toll-Like Receptor 2 (TLR-2)/Nuclear Factor-Kappa B (NF-κB) signaling pathway. Collectively, our work underscores VTX’s promising role in enhancing motor, cognitive functions, and mitigating depressive symptoms following cerebrovascular accidents, potentially through inflammation regulation. These insights pave the way for novel interventions addressing post-stroke complications, warranting further exploration.